The impingement boiling heat transfer of liquid nitrogen onto superheated tube array - Yonathan, Gayus (2015)
Jet impingement heat transfer is a common topic for which many researches had been done. From its concept to its application on thermo acoustic stirling engine, it had been studied under different field of study such as fluid dynamics, thermodynamics, etc. In this report, it introduces how heat exchanger is applied or its implication in stirling engine. After that, there are short reviews about previous study of jet impingement, thermodynamic concept, heat transfer concept and heat exchanger design principle and phase change. It is including reviewing previous research which mainly jet impingement with single phase fluid. Phase change through boiling heat transfer is introduced and be the main topic in this study. This study includes two parts of methodology. In first part, it is discussing the suitable design of heat exchanger for stirling engine. It decides the multi inlets and outlet which can convey liquid nitrogen and its vapour. It must be designed to sustain the pressure and temperature as it is involving cryogenic temperature. The second part will be discussing about meshing and how to set the simulation parameter as numerical study will need the parameter of boundary condition. For instance, setting velocity to 0.5m/s and it gives convective heat transfer coefficient 13.89 W/m2. It has different value for the other 2 setting of velocity and setting of constant temperature wall. For the detailed results, it can be seen in table 4. In following chapter, results and discussions of CFD (Computational Fluid Dynamics) simulation is presented. This simulation is run using ANSYS and observed through it parameter temperature, heat flux, velocity and inlet interaction, etc. After all, conclusions and recommendation will be given in the last part to improve all factors and minimize error before the real experiments.